Mental health in the community – Malaysia: a 20-year journey of a family medicine consultant - Mohd Sidik, Sherina (Universiti Putra Malaysia Press, 2017)
Mental health is more than the absence of mental illness. It is a state of well-being in which a person realises his or her own abilities, can cope with the normal stresses of life, can work productively and is able to make a contribution to his or her community. Mental health includes: • How someone feels about him / herself • How someone feels about other people • How someone is able to handle the demands of life. One way of describing mental health is to describe mentally healthy people. To be mentally healthy, a person needs to have a balance of protective individual and community factors. Protective individual factors are high self-esteem, good coping mechanisms, a sense of meaningful life, effective communication, strong social network and a sense of humour, whereas protective community factors are safety, healthy physical environment, adequate resources and a sense of community. Mental health is thus the foundation for individual well-being and the effective functioning of a community.